Cognitive/affective and somatic/affective symptoms of depression in patients with heart disease and their association with cardiovascular prognosis: a meta-analysis. Issue 13 (27th January 2014) - de Miranda Azevedo, R.; Roest, A. M.; Hoen, P. W.; de Jonge, P.
Abstract : Background: Several prospective longitudinal studies have suggested that somatic/affective depressive symptoms, but not cognitive/affective depressive symptoms, are related to prognosis in patients with heart disease, but findings have been inconsistent. The aim of this study was to investigate the association of cognitive/affective and somatic/affective symptoms of depression with cardiovascular prognosis in patients with heart disease using a meta-analytic perspective. Method: A systematic search was performed in PubMed, EMBASE and PsycInfo. Thirteen prospective studies on symptom dimensions of depression and cardiovascular prognosis fulfilled the inclusion criteria, providing data on a total of 11 128 subjects. The risk estimates for each dimension of depressive symptoms, demographic and methodological variables were extracted from the included articles. Results: In least-adjusted analyses, both the somatic/affective [hazard ratio (HR) 1.30, 95% confidence interval (CI) 1.19–1.41, p < 0.001] and cognitive/affective (HR 1.07, 95% CI 1.00–1.15, p = 0.05) dimensions of depressive symptoms were associated with cardiovascular prognosis. In fully adjusted analyses, somatic/affective symptoms were significantly associated with adverse prognosis (HR 1.19, 95% CI 1.10–1.29, p < 0.001) but cognitive/affective symptoms were not (HR 1.04, 95% CI 0.97–1.12, p = 0.25). An increase of one standard deviation (±1 s.d. ) in the scores of the somatic/affective dimension was associated with a 32% increased risk of adverse outcomes (HR 1.32, 95% CI 1.17–1.48, p < 0.001). Conclusions: Somatic/affective depressive symptoms were more strongly and consistently associated with mortality and cardiovascular events in patients with heart disease compared with cognitive/affective symptoms. Future research should focus on the mechanisms by which somatic/affective depressive symptoms may affect cardiovascular prognosis.